EVOLUTION OF THE CONCEPT “MASS CULTURE” ON THE WAY TO POSTINDUSTRIAL SOCIETY - Кононенко, О. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The state reveals the essence of mass culture as a special public phenomenon, special features of its mechanisms and algorithms of development.